Fraud Analysis in Village Fund Management from the Perspective of Fraud Hexagon Theory in Buton Regency - Nur Azkia; Ishak Awaluddin; Tuti Darmawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research sets out to have a proper look at how the Fraud Hexagon elements shape dodgy practices in village fund management. A quantitative, explanatory approach is used, with first-hand data gathered through questionnaires handed out to selected village officials in Buton Regency via purposive sampling. The predictors cover pressure, opportunity, rationalisation, competence, arrogance, and collusion, while the outcome of interest is fraud involving village funds. The numbers were then crunched using multiple linear regression. The results show that all elements of the Fraud Hexagon have a positive and significant effect on fraud in village fund management. This finding confirms that fraud is influenced by a combination of structural, behavioral, and social relational factors within village organizations. This study strengthens the application of the Fraud Hexagon theory in the public sector and provides practical implications for strengthening internal control and village financial governance.